When Speed Breaks the Sound Barrier: The Effect of Cue Hierarchy on Expected Quality and Purchase Intentions Regarding Laptops - Piermattéo, Anthony; Lo Monaco, Grégory; Delouvée, Sylvain (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
A few taxonomies have been proposed to categorize the cues consumers use to assess the quality of a given product. However, these taxonomies do not take into account the possible hierarchy that may exist among these cues. Through three studies we tested a taxonomy based on the structural approach to social representations. This framework proposes a distinction between central and peripheral cues. The former would be essential whereas the latter would be less important in the process of conducting quality assessment or with regard to purchase intentions. Results show that, concerning purchase intentions, a good central feature can compensate for a poor peripheral feature while the converse is not possible. Moreover, this interaction effect is mediated by the perceived quality of the product.